(untitled) (Papeles, 2021)
Local governments deploy a broad set of youth policies and develop different types of institutions to address the youth issue in their communities. This work proposes a categorical classification for their systematic interpretation: social protection and youth welfare systems. It is analyzed with a comparative qualitative study on the analytical power of the typological theory built through the historical reconstruction of youth policies designed and implemented in two municipalities in the province of Córdoba, Argentina. In addition, it investigates the factors that affect the formation and development of social protection and youth welfare systems. The research carried out starts from the hypothesis that these depend on the characteristics acquired by the government projects in charge of local administrations, mediated by the state capacities willing to address the youth and by the influence exerted by extra-state actors on the dynamics local politics. The article presents the main findings from the proposed analytical framework.